2008
DOI: 10.1371/journal.pmed.0050253
|View full text |Cite
|
Sign up to set email alerts
|

A Randomised Controlled Trial of Artemether-Lumefantrine Versus Artesunate for Uncomplicated Plasmodium falciparum Treatment in Pregnancy

Abstract: BackgroundTo date no comparative trials have been done, to our knowledge, of fixed-dose artemisinin combination therapies (ACTs) for the treatment of Plasmodium falciparum malaria in pregnancy. Evidence on the safety and efficacy of ACTs in pregnancy is needed as these drugs are being used increasingly throughout the malaria-affected world. The objective of this study was to compare the efficacy, tolerability, and safety of artemether-lumefantrine, the most widely used fixed ACT, with 7 d artesunate monotherap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
195
5
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 127 publications
(213 citation statements)
references
References 42 publications
11
195
5
2
Order By: Relevance
“…However, the observed lower-than-average lumefantrine concentrations in the few patients with treatment failure who had pharmacokinetic sampling are in agreement with several reports from studies in Thailand and Papua New Guinea showing that the lumefantrine plasma level is a key determinant of A-L efficacy (8,12,16,22).…”
Section: Discussionsupporting
confidence: 91%
“…However, the observed lower-than-average lumefantrine concentrations in the few patients with treatment failure who had pharmacokinetic sampling are in agreement with several reports from studies in Thailand and Papua New Guinea showing that the lumefantrine plasma level is a key determinant of A-L efficacy (8,12,16,22).…”
Section: Discussionsupporting
confidence: 91%
“…The day 63 PCR-adjusted cure rate for P. falciparum was high and similar to the rates in previous studies in nonpregnant women (38), and it was slightly higher than observed when DHA-PPQ was used as rescue treatment in pregnancy in the same population (27). Inferior cure rates in treating recrudescent infections in pregnant women have been reported before (16).…”
Section: Discussionsupporting
confidence: 84%
“…Overall, the optimized SNEDDS formulation showed significantly lower (p50.001) mortality rates as compared to that of the pure drug, indicating superior treatment efficacy of the developed formulations. The observed results are in consonance with literature showing increased efficacy of artemether when administered in nanoformulations (McGready et al, 2008;Cachet et al, 2009). …”
Section: In Vivo Pharmacodynamic Studiessupporting
confidence: 91%